The Interest Rate, Learning, and Inventory Investment - Maccini, Louis J; Moore, Bartholomew J; Schaller, Huntley (American Economic Review, 2004)
This paper presents a model that provides an explanation, based on regime switching in the real interest rate and learning, of why tests based on stock-adjustment models, Euler equations, or decision rules—which emphasize short-run fluctuations in inventories and the interest rate—are unlikely to uncover a negative relationship between inventories and the real interest rate. The model, however, predicts that inventories will respond to long-run movements, that is, to regime shifts in the real interest rate. Tests emphasizing cointegration techniques confirm this prediction and show a significant long-run relationship between inventories and the real interest rate.